MULTI-COMPONENT COMPLEX ORE: LEGAL PROBLEMS OF TAXATION - VERSHILO Nikolay Dmitrievich; VERSHILO Tatyana Alexandrovna (Правовое государство: теория и практика)
Finding an optimal balance of public and private interests in taxation is a task that must be addressed by the state, which seeks not only to increase tax revenues to the budget, but also to create optimal tax conditions for business and production development. Therefore, the analysis of the problems of legal regulation of mineral extraction tax (MET) in the extraction of multi-component complex ores, including the determination of the item and rate of taxation, and the search for their optimal solutions is aimed at improving tax legislation in the context of tax reform. Purpose: to analyse the problems of legal regulation of MET payment for the extraction of multi-component complex ores, including in determining the item and rate of taxation. Methods: empirical methods of description, interpretation; theoretical methods of formal and dialectical logic; specific scientific methods: legal-dogmatic and interpretation of legal norms. Results: the study reveals that there is no definition of the concept of «multi-component complex ore» in the provisions of the legislation on taxes and levies, as well as in sectoral regulations, therefore, it cannot be considered that such an item of taxation is defined and established by the legislator. The letters received by the tax authority from the Federal Agency for Subsoil Use (Rosnedra) are not regulatory acts and cannot be used as a basis for the regulatory authorities’ conclusions during tax audits. The analysis of the law enforcement (judicial) practice since 2002, as well as certain provisions of regulatory legal acts show that polymetallic ores containing non-ferrous and/or precious metals have historically been qualified as complex multi-component ores. Therefore, the authors propose to amend the tax legislation, taking into account the additional characteristics of multicomponent complex ores when they are mined.